Outplacement - Barriers and Challenges of Implementation by Small and Medium-Sized Enterprises in Poland - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (Poznań University of Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Under the conditions of the global financial and economic crisis restructuring undertaken by companies often is associated with the optimization of operating costs in the dimension of human capital. Relatively little popular technique is responsible outplacement, which can reduce the risk of long-term unemployment and maintains the key competencies by the employees and organizations. At the same time public and private employment services usually have no experience in implementing outplacement programs. Small and medium-sized enterprises have difficulties in availability of those services. This paper is based on a critical analysis of the literature and a study conducted in Podlaskie Voivodship in 2012 under the project 'Innovations in the corner – testing and implementation of new methods of outplacement'. The study included a series of in-depth interviews, focus groups and quantitative CATI research among entrepreneurs and employees. Main conclusions lead to the claim that outplacement should be popularized as good practice of corporate social responsibility. The implementation of such programs can be done by increasing the role of social economy actors – in particular non-governmental organizations that carry out tasks in the field of labor market policy. – – W warunkach globalnego kryzysu finansowego i gospodarczego podejmowana przez przedsiębiorstwa restrukturyzacja wiąże się często z optymalizacją kosztów działalności w wymiarze kapitału ludzkiego. Relatywnie mało popularną jest technika odpowiedzialnych zwolnień monitorowanych, która umożliwia ograniczenie ryzyka długotrwałego bezrobocia oraz pozwala na zachowanie kompetencji kluczowych tak przez pracowników, jak i organizacje. Jednocześnie publiczne i niepubliczne służby zatrudnienia przeważnie nie mają doświadczenia w realizacji programów outplacement. Programy te są też trudno dostępne dla małych i średnich przedsiębiorstw. Referat opiera się na krytycznej analizie literatury przedmiotu oraz badaniach przeprowadzonych w województwie podlaskim w 2012 roku w ramach projektu ,,Innowacje na zakręcie - testowanie i wdrażanie nowych metod outplacementu”. Badania obejmowały serię indywidualnych wywiadów pogłębionych, zogniskowanych wywiadów grupowych oraz badanie ilościowe CATI wśród przedsiębiorców i pracowników. Główne wnioski prowadzą do twierdzenia, iż outplacement powinien być upowszechniany jako dobra praktyka społecznej odpowiedzialności biznesu. Realizacja programów może odbywać się poprzez zwiększenie roli podmiotów gospodarki społecznej - w szczególności organizacji pozarządowych realizujących zadania z zakresu polityki rynku pracy.
Conference: 11th Annual ESPAnet Conference “Social Policy and Economic Development”, September 5-7, 2013, Poznań University of Economics
Keywords: E24; G34; M54; R58; 330; activation policy; restructuring anticipation; unemployment; outplacement stakeholders; local partnerships and pacts; regional and local development; cross-sectoral cooperation; outplacement; unemployment; social change; urban economics